Students Error Description and Contributing Factor in Solving TIMSS Geometry Content Domain Problems Based on Their Learning Style - Hendri Maulana; Ipah Muzdalipah; Depi Setialesmana; Rina Musannadah; Lazna Suci Wali (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2023)
Using Newman Error Analysis (NEA) theory, this study aims to describe the errors made by students when solving TIMSS geometry content domain problems. Six eighth-grade students from a junior high school in Tasikmalaya consists of two students from each of the three learning styles (visual, auditory, and kinesthetic) were used as research subjects in a descriptive qualitative study during the academic year 2019/2020. The data were collected remotely through Zoom and Skype as the research was conducted during the earlier phase of COVID-19 pandemic. Three problems from the geometry content domain of the TIMSS 2015 test, unstructured interviews, and learning style questionnaires developed by the Ministry of Education and Culture of the Republic of Indonesia were the instruments used to collect data. The study results indicate that visual-style subjects made no errors during the reading stage, whereas almost all subjects made errors during the other stages. The most highlighted causes of errors were a lack of concept comprehension and neglecting prerequisite materials related to the required concepts. Mathematics teachers should consider this description when designing instructional strategies to reduce students' problem-solving errors.